(untitled) (Innovaciones Educativas, 2025)
The university deserves to consider the development of competencies necessary for transformation. The objective of this paper is to describe the development of leadership competencies in academic training at the River Plate University Institute (2021-22). The analysis is configured from the hermeneutic phenomenology of the social sciences, through the interpretation of the webs of meaning in the university. It is a study with a critical and unique character, through a purposive sampling of 12 people, where interviews, focus groups and institutional documents are analyzed. The model of educational leadership competencies in this work considers: Strategic thinking, learning management, relationship with people and creating and animating organizational structures. As a result, the development of institutional leadership competencies is characterized by presenting characteristics of greater permeability due to its proximity to its genesis. This gives it a more flexible basis in the face of high bureaucracy and less resistance to changes and innovations that emerge for the improvement of education. It is concluded that the perspective of the academic community represents a recognition of the efforts and work carried out through strategic objectives in the search for the improvement of educational quality, growth, development of its areas and institutional expansion.